Factors That Influence Behavior Intention of Z Generation in Choosing Products of Cellular Telecommunication Services - Ardi W. Alfan; Fadil P. Satria; Shu-Chiang Lin (IPTEK Journal of Proceedings Series, 2020)
This research studies about Behaviour Intention of Z Generation in choosing cellular telecommunication services product. Using combination of Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and Structural Equation Modeling (SEM) method. UTAUT2 is commonly used to review the acceptance of information technology product, then SEM can provide lear picture of the relationship between variables. After data processing, can be seen if some independent variabels are significantly influence to dependent variables. Effort Expectancy, Price Value, Habbit are significantly influence to Behavioral Intention with the value of 0,3, 0,2, and 0,8. Then habbit also significantly influence Use Behavior with the value of 0,49. The aim of this research is to be able to find out which variables that can influence the intention behaviour of Z Generation for choosing the cellular telecommunication services product so than can be uset for operators as reference in taking strategic step of product development.